IMPACT OF MARKET INFRASTRUCTURE ON BUSINESS ACTIVITY IN UKRAINE DURING WAR - Бойчик, Віталій Є. (Journal of Strategic Economic Research, 2023)
The article examines the influence of various elements of the market infrastructure on the state and development of entrepreneurship in Ukraine in the conditions of military operations. The purpose of the article is to identify the functions of the market infrastructure and to study the influence of its various elements on the state, potential possibilities of functioning and prospects for the development of small and medium-sized enterprises in Ukraine after the full-scale invasion of the Russian Federation on the territory of our state. The main research methods are the grouping method – when studying the functions of the market infrastructure and their classification; the method of analysis and synthesis – when researching the levels of market infrastructure and their elemental content; the method of deduction and induction – when considering the impact of individual elements of the market infrastructure on entrepreneurial activity in Ukraine in the conditions of military operations; graphic method – for visualization of individual research results. The analysis of public statistical information made it possible to state that Ukrainian business has demonstrated the ability to maneuver even under the conditions of the most difficult situations. It has been studied that small and medium-sized businesses are affected by the state of the market infrastructure, which itself has undergone significant destruction. Attention is focused on the classification of market infrastructure functions, the main ones are highlighted and characterized. It was found that not all elements of the market infrastructure are equally relevant for the business sector in the conditions of military operations. The levels of the market infrastructure (micro-, meso-, macro-level) and their content are highlighted. It has been studied that for specific business entities in specific conditions, various elements of the market infrastructure are prioritized. In the conditions of war, the material elements of the market infrastructure have the greatest influence on the business sector of the state, among which road management, energy, communications, and the field of logistics (transport, roads, ports, the possibility of transportation, etc.) are highlighted. The completeness and quality of the provision of administrative services, social security of the population, education, health care, which was caused by the processes of relocation of enterprises from «hot zones» and internal displacement of the population, also increased the impact on entrepreneurship. Highlighting the role and development opportunities of trade as a market intermediary and the sphere of service provision; elements of the institutional infrastructure, especially in terms of supporting entrepreneurship, including through grant funding, preferential lending, etc.